Long-term fate of the coronary arteries after the arterial switch operation in newborns with transposition of the great arteries. Issue 3 (September 1996) - Bonnet, D.; Bonhoeffer, P.; Piéchaud, J. F.; Aggoun, Y.; Sidi, D.; Planché, C.; Kachaner, J.
Abstract : OBJECTIVE: Concern continues to be expressed about the long-term impact of coronary artery translocation after the arterial switch operation for transposition of the great arteries. This study was conducted to determine the prevalence of obstructions of the translocated coronary arteries by the use of selective coronary artery angiography. METHODS AND RESULTS: 64 children (mean age 7.6 (SD) 1.5 years) who had survived an arterial switch operation underwent evaluation. They had been operated on by one surgeon and they were followed up by a single hospital. Selective coronary artery angiography was possible in 58 patients. Five patients showed occlusion or stenosis of a coronary artery: one occlusion and two stenoses of the left coronary trunk, two occlusions of the circumflex artery. The prevalence of late coronary artery complications was 7.8 (SD) 6.6% (95% CI 1.2 to -14.4%). The three patients with occlusion of one coronary artery had perioperative ischaemic complications, with associated electrocardiogram evidence of ischaemia and left ventricular dysfunction with mitral valve insufficiency. Both patients with stenosis of the left main coronary artery trunk did not have any evidence of an anomaly before catheterisation. CONCLUSIONS: The prevalence of the late coronary artery complications after an arterial switch operation was low in this series. This accords with the view that the arterial switch operation remains the preferred treatment for such patients. Screening for late coronary artery patency should be done by using selective coronary artery angiography, because even patients who remain symptom free can have coronary artery anomalies.